Assessment of Potential Toxicity of Onion-like Carbon Nanoparticles from Grilled Turbot Scophthalmus maximus L. - Zuzhe Wang; Jingran Bi; Haitao Wang; Mingqian Tan (Foods, 2021)
Although the presence of foodborne nanoparticles was confirmed in grilled fish in a previous study, the evaluation of potential health risks of these NPs was insufficient. In the present study, the potential toxicity of onion-like carbon nanoparticles (OCNPs) separated from grilled turbot Scophthalmus maximus L. was evaluated using mouse osteoblasts cells model and zebrafish (Danio rerio) model. Cytotoxicity evaluation revealed that the OCNPs penetrated into the MC3T3-E1 cells without arousing cell morphology changes. No evident apoptosis or damage of cells was observed with increasing OCNPs’ concentration to 20 mg/mL. In the hemolysis test, OCNPs did not show an obvious hemolysis effect on red blood cells. In the acute toxicity test, the LC50 value (212.431 mg/L) of OCNPs to zebrafish showed a weak acute toxicity. In subacute toxicity test, after exposure to OCNPs (30 mg/L, 40 mg/L) for 10 days, a significant increase of reactive oxygen species level of zebrafish was observed. Meanwhile, redundant ROS content caused inhibition to several antioxidant enzymes and induced lipid and protein peroxidation damages according to the upregulation of malondialdehyde and protein carbonyl levels. The chronic toxicity test results indicated that oxidative stress was only observed in the high concentration group of OCNPs-treated zebrafish.